The role of grievance in fatal family violence and implications for the construct of lone actor grievance-fuelled violence - Cooper, Alannah J.; Pathé, Michele T.; McEwan, Troy E. (Frontiers in Psychology, 2022)
The concept of lone actor grievance fuelled violence assumes that homicides that occur in very different contexts can be thought about in a consistent manner because they share common motivations and resultant emotional states like resentment, outrage or revenge. Fatal family violence has been largely excluded from discussions of lone actor grievance-fuelled homicide, based on the assumption that it is conceptually different. This scoping review examines similarities and discrepancies between the characteristics and motivations of perpetrators of fatal family violence and those who have engaged in lone actor grievance-fuelled homicide outside the family context, and the relevance of the concept of grievance-fuelled violence to fatal family violence. This study reviewed published case studies and case series, resulting in a dataset of 102 homicide cases from 36 studies, of which there were 38 fatal family violence cases and 64 categorised as lone actor grievance-fuelled homicide. Twenty of the 38 fatal family violence cases were identified as being grievance-fuelled, based on the presence of motivations consistent with definitions in the grievance literature. While there were some offence similarities between the fatal family violence cases (e.g. location of offence), those driven by grievance were more similar to lone actor grievance-fuelled homicide in other ways (e.g., offender’s gender and offence methods). In both these categories violence was predominantly motivated by grievance and a desire for revenge, whereas non-grievance fatal family violence cases were predominantly motivated by altruism. The motivations that defined behaviour as lone actor grievance-fuelled homicide were equally apparent in a sub-group of fatal family violence, implying that some family violence cases can be integrated into the construct of lone actor grievance-fuelled homicide in future research and theorising.